Geotechnical Assessment of Soil at the Campus Site of College of Science, University of Diyala - Hassan, Asem; Khwedim, Kareem; Sahaab, Abdalratha (Iraqi Journal of Science, 2022)
In this study, some physical and mechanical properties of soil samples collected from the campus site of College of Science, University of Diyalahave been evaluated. All laboratory tests were performed according to the standards of American Society for Testing and Materials (ASTM). The test results showed that the range of soil water content wwas (13.89%-16.34%) with an average of 15.44%. The specific gravity range was (2.58-2.77) with an average of 2.66. The range of Liquid Limit LL was (26.20-35.20%) with an average of 32.22%.The range of Plastic Limit PL was (18.63-23.24%) with average of 21.06%. The range of Plasticity Index was (7.57-12.42) with an average of 11.61. Based on USCS classifications, the soil can be considered as fine-grained soil type CL (CL is inorganic clay soil of low to medium plasticity). Liquidity Index LI values were ranged from 0.002 to 0.560 while Consistency Index CI ranged from 0.271 to 0.998 indicating a plastic state. The average optimum water OWC content and maximum dry density MDD calculated from Standard Proctor Compaction test were 10.36% and 1.79g/cm3, respectively. Shear test results revealed that the cohesion strength range was (5-10 Kg/m2) with an average of 7.8 Kg/m2, and the angle of internal friction range was (25-30o) with an average of 29.4o. The measured values of angle of internal friction are within the range of CL soil. However, the cohesion strength is relatively low as cohesion of clay soil is affected by different factors such water content and clay content. The compression index derived from consolidation test was ranged from 0.03 to 0.25, and the calculated values of void ratio (0.94-1.04) and porosity (0.48-0.51) are within the range of clay soils. Physical and mechanical properties presented in the current study are useful for future engineering works scheduled at the campus site of College of Science,University of Diyala.